1999
DOI: 10.1007/s001340050996
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic colony-stimulating factors for neutropenic patients in the ICU

Abstract: H-CSF for treatment of neutropenia in patients admitted to the ICU did not accelerate neutrophil recovery or improve survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 9 publications
(5 reference statements)
0
5
0
Order By: Relevance
“…Conversely, use of G-CSF in patients with already overt infections (curative G-CSF) was found to have a limited benefit in neutropenic patients [ 58 , 59 ]. Data regarding interest of prophylactic or curative use of G-CSF are limited to studies with high risk of bias and suggest a limited efficacy in this setting [ 60 62 ]. In addition, G-CSF remains associated with potential side effects, including risk of worsening respiratory status during neutropenia recovery [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, use of G-CSF in patients with already overt infections (curative G-CSF) was found to have a limited benefit in neutropenic patients [ 58 , 59 ]. Data regarding interest of prophylactic or curative use of G-CSF are limited to studies with high risk of bias and suggest a limited efficacy in this setting [ 60 62 ]. In addition, G-CSF remains associated with potential side effects, including risk of worsening respiratory status during neutropenia recovery [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that 30-day mortality was 58% in our 102 CICPs, of whom 91 (89.2%) received MV, 67 (65.7%) vasopressor agents, and 28 (27.4%) dialysis. Few studies have been specifically designed to identify predictors of death in neutropenic CICPs [19,20,24]. Blot at al.…”
Section: Discussionmentioning
confidence: 99%
“…In two studies that used univariate analysis, G-CSF therapy had no effect on in-ICU neutropenia duration in CICPs [19,20]. The statistical methods used in these studies failed to take into account the time-dependency of NR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In meta-analyses performed in patients with non-Hodgkin’s lymphoma or solid tumors, use of G-CSF was associated with a decrease in both overall mortality and infection-related mortality [ 135 – 137 ]. Little data on this topic in the ICU are available, suggesting limited efficacy in this setting [ 72 , 138 ], and it was obtained from studies with low-level evidence. Thus, despite uncertainties and while additional studies are needed, it seems reasonable to recommend using prophylactic G-CSF when available or deemed necessary by an oncologist or hematologist.…”
Section: Hematological Managementmentioning
confidence: 99%